Leukocyte and thrombocyte reference values for channel catfish (Ictalurus punctatus Raf), with an assessment of morphologic, cytochemical, and ultrastructural features - Tavares-Dias, Marcos; de Moraes, Flavio Ruas (Amer Soc Veterinary Clinical Pathology, 2007)
Background: Hematology tests are useful to evaluate physiologic disturbances in fish and can provide important information for the diagnosis and prognosis of disease. Objectives: the primary purpose of this study was to define reference intervals for thrombocytes and leukocytes in healthy channel catfish (Ictalurus punctactus). In addition, the morphologic, cytochernical, and ultrastructural features of blood cells were assessed. Methods: Blood samples (0.5 mL were collected into EDTA from 40 clinically healthy catfish on a commercial fish farm in Jaboticabal, Brazil. Thrombocyte, total WBC, and differential WBC counts were determined and reference intervals were calculated as the 25-95th percentiles of data. Thrombocyte and leukocyte morphology was assessed in blood smears stained with May Griinwald-Giemsa-Wright and ultrastructurally by transmission electron microscopy. Cytochemical staining patterns were described using periodic acid-Schiff (PAS), peroxidase, nonspecific esterase, alkaline phosphatase, and toluidine blue. Results: Reference intervals were as follows: thrombocytes 58,802-99,569/mu L; total WBCs 27,460-41,523/mu L; lymphocytes 5380-11,581/mu L; monocytes 2949-7459/mu L; neutrophils 12,529-22,748/mu L, and basophils 736-2003/mu L. Neutrophils were positive for peroxidase and PAS; monocytes were positive for nonspecific esterase; and basophils were positive with toluidine blue. Conclusion: the morphologic and staining features of neutrophils and monocytes of channel catfish are similar to those of mammals, and the presence of basophils in this species was verified. These reference intervals and morphologic findings provide a foundation for future investigations on the functions and alterations of blood cells in channel catfish.
Keywords: channel catfish; cytochemistry; fish; hematology; leukocytes; ultrastructure